Counselling the Borderline Client: An Interpersonal Approach - Angus, Lynne; Gillies, Laurie A. (Canadian Journal of Counselling and Psychotherapy, 2007)
Characteristics thought to be associated with "difficult clients" are critically reviewed in light of research findings emerging from the psychiatric and psychological literature pertaining to Borderline Personality Disorder. Recent developments for brief treatment strategies are reviewed and the development of a short term interpersonal therapy programme is described. Potential strengths and weaknesses of this treatment approach for counselors are discussed.